Impurity and defect mitigation for silicon photovoltaics - Martins, G (2016)
This thesis details a number of techniques designed to improve the efficiency of solar cells by reducing the impact of efficiency-limiting defects. The defects targeted by this work include transition metal impurities located within the as-cast silicon wafer, and dangling silicon bonds located at the wafer surfaces. This thesis has been divided into three techniques that have been studied. Firstly, saw damage gettering which is designed to remove impurities from low quality silicon wafers which may have otherwise been discarded. Saw damage gettering removes impurities from the active region of the solar cell by capturing them in a surface region which can then be removed before solar cell processing. This technique therefore allows low quality silicon wafers to be 'upgraded' such that they can be re-introduced into conventional processing lines. In this thesis it has been shown that saw damage gettering can stably reduce the iron concentration in wafers, a notable factor in reducing solar cell efficiency. It has been shown that this technique can result in a 68% reduction in iron concentration, even after further thermal processing. Secondly, gas phase gettering is a technique that removes impurities from the silicon wafer by enabling the impurities to react with a gaseous atmosphere which can then be removed from the silicon. In this work, the thermodynamics and kinetics of reactions between impurities and gettering agents are investigated and an optimal gettering agent, molecular chlorine, is proposed. Gas phase gettering using this species was then tested and found to enable gettering at all temperatures trialled. It was seen to reduce iron concentrations to the detection limit, which is notably a reduction in interstitial iron concentration of three orders of magnitude. The final technique developed was shielded hydrogen passivation. In this technique, monatomic hydrogen is provided to a silicon/dielectric interface where it reduces the density of dangling bonds, improving the cell efficiency. The monatomic hydrogen is provided by a plasma, which can introduce damage to the surface regions. A significant body of this work was focussed on mitigating this damage, without preventing the passivation process. Ultimately, shielding the samples with palladium enabled very high lifetimes of 4 ms on 1 Ωcm n type material.